The Roles of Wattpad towards Writers in Malaysia - Syuhaidah Ayub, Nur; Syuhaidi Abu Bakar, Mohd; Jaafar, Fazlina (International Journal of Academic Research in Progressive Education and Development, 2023)
Wattpad is one of many applications allowing users to read, write, and interact on the same application. In this modern age, writers have many options for how they want to write, whether they use traditional ways to write and publish or modern ways, using applications like Wattpad to broaden their potential to publish. Wattpad has many roles that can be useful to writers, as seen in other countries. Therefore, this paper has explored the roles of Wattpad towards writers in Malaysia by interviewing 11 informants who are users of Wattpad. Findings show Wattpad has four leading roles, which are the role as a community platform for writers and readers, the role for gathering creative writing and acting as a promoting platform, the role of helping writers write from traditional to technology-based writing, and lastly, supporting Malaysian creative writing.